PERBANDINGAN PERAN PEKERJA PRIA DAN PEKERJA WANITA TERHADAP JUMLAH HASIL KERJA MEMETIK DAUN TEH - Alfianto, Eko Agus; Fazizah, Amma (Program Studi Ilmu Administrasi Bisnis, UPN Veteran Yogyakarta, 2019)
The problem of labor that is crammed into life is still a big problem and needs to be resolved. Employment control by male workers is an important part of achieving goals for the job itself. The main consideration of the use of male workers is that male workers have longer working hours and no time constraints such as female workers. Male workers have a greater power qualification than female workers, so male workers are the main choice and consideration for employment. Gardens wonosari tea district Lawang Malang regency, has now been employing many women workers as tea pickers. Working as tea pickers, in general can be done by male and female workers. This research is a quantitative research with descriptive and inferential approach. The research location is tea garden of wonosari PTPN XII Lawang with male worker object and female picker tea workers. X1 variable is male worker and X2 variable is female worker. The result of data processing by using SPSS shows that for variable X1 all question items are declared valid. Likewise, the reliability of data for variebel X1 otherwise reliable with alpha of 0.919 and varibel X2 with an alpha value of 0.688. While the regression value of Y = -1.055 + 0.162 XI + 0.214 X2 + 1.32749 and R Square / coefficient of determination which shows the value of 0.817 or 81.7%. This means that the contribution of male and female workers is 81.7%. and the rest is influenced by another variable of 18.3% outside the independent variables studied. Keywords: labor, male workers, female workers.